ANALISIS PENGARUH DISIPLIN DAN KOORDINASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PENDAPATAN DAERAH ( DISPENDA KOTA PONTIANAK ) - B11108096, Trianto (Jurnal Manajemen Update, 2013)
The objective of the research is finding out how is the significant of Discipline and Coordination against the Staffs working performance of employee in Government Service Regional Income Office of Pontianak city both partially and stimulatingly, and the contribution of discipline and coordination through Staffs Working Performance. The research is conducted in Government Service Regional Income Office of Pontianak city in Jalan Gusti Sulung Lelanang No. 1B, Pontianak City. Research method on this thesis is Survey Research; where the questionnaires are used as the main tool of data collection. The population of this research is the whole Office Staffs except the Chief of this Government Service in 2009-2011. The samples are taken by using Saturation Sampling/Census, in which the members of population are taken in the number of 74 respondents. Collected data is analyzed by using Double Linear Regression Analysis Method and Path Analysis on the significant level of 5% (? = 0,05). The result of Hypothesis testing shows that Partial and stimulant discipline and coordination are significantly influential against staffs working performance. The collective significant level of discipline and coordination is 62,2% and the rest 37,8% is influenced by other factors which are not explained in this research. Keywords: Discipline, Coordination, and Working Performance.